Outcome of pregnancy in women with cystic fibrosis. Issue 2 (February 1995) - Edenborough, F P; Stableforth, D E; Webb, A K; Mackenzie, W E; Smith, D L
Abstract : BACKGROUND–As women with cystic fibrosis are living longer, pregnancy is becoming increasingly common. The combined experience of pregnancies in women with cystic fibrosis from adult centres in the Midlands and North of England has been examined. METHODS–A retrospective study of the case notes of 22 pregnancies in 20 patients with cystic fibrosis examined changes in lung function, body weight, and microbiological status during the course of pregnancy. Duration of pregnancy, birth weight, and maternal survival were amongst other variables studied. The relation between values before pregnancy and important outcome measures were examined. RESULTS–Eighteen of 22 pregnancies were completed producing healthy, non-cystic fibrosis infants (12 female). Mothers lost 13% of FEV1 and 11% of FVC during pregnancy, most of which was regained. Body weight changes were variable, but most mothers gained weight (mean weight gain 5.7 kg). Microbiological status remained unchanged. Six infants were preterm and two were light for dates. Four mothers died up to 3.2 years following delivery. Of the prepregnancy parameters examined, %FEV1 showed the best correlation with maternal weight gain, gestation, birth weight, and maternal survival. CONCLUSIONS–Pregnancy was well tolerated by most mothers with cystic fibrosis although those with moderate to severe lung disease (%FEV1 < 60%) before pregnancy fared worse, producing preterm infants and suffering increased loss of lung function and mortality compared with mildly affected mothers. Prepregnancy %FEV1 appears to be the most useful predictor of important outcome measures in pregnancies in women with cystic fibrosis.